Health Appraisal of The Forest Guards and Scalers - A Study from Uttarakhand, India - Rajesh Kumar Singh; Mehar Bano; CMS Rawat (Medsci Publications, 2015)
Background: The forestry personnel such as forest guards and scalers are one of the human resource serving in the forests, na- tional parks in India. They work in difficult terrains and are ex- posed to adverse environmental conditions. They are responsible for protection of forest resources and prevention of any illegal activities like felling of trees, poaching, encroachments, grazing, forest fires etc. and a step is required regarding their health pro- file in India. Objective of the study was to know the morbidity profile and certain selected lifestyle related risk factors of non- communicable diseases among forest guards and scalers. Methods: The present cross-sectional observational study was conducted among forest guards and scalers at forest Training In- stitute, Haldwani, Uttarakhand. Clinical history   was   recorded and relevant physical examination was carried out. Parameters like weight, height, and blood pressure were recorded. Results: In the present study, 88 forest guards and scalers were studied, out of which 74% were male. Addiction was present in 53.4% of participants. 40% of participants were found to be over- weight and obese.20% of the participants were hypertensive and about 4.5% of them reported to be diabetic. About one-fifth (20.5%) had GI problems and 12.5% of them had various muscu- lo-skeletal problems. Conclusion: Addiction to alcohol and tobacco was found in ma- jority of the male participants. Lifestyle related risk factors of non- communicable diseases were seen so periodic health examina- tions and sensitization regarding maintenance of healthy lifestyle needs to be encouraged.